Making something out of nothing: Breaching everyday life by standing still in a public place. Issue 6 (November 2020) - Stanley, Steven; Smith, Robin James; Ford, Eleanor; Jones, Joshua
Public displays of stillness and silence are increasingly found in contemporary life, yet have seldom been examined as social phenomena in their own right. We analyse people's accomplishment, treatment and negotiation of an encounter with people 'doing nothing' – a breaching experiment comprising a group of students standing still in a city centre – and provide a granular description of the bodily practices whereby passers-by make 'something' out of 'nothing'. Our ethnomethodological analysis of video recordings of the event demonstrates three practices for doing embodied noticing - looking back; slowing and pausing; stopping still - and illustrates how passers-by engage in 'audiencing' and 'performing'. We propose breaching experiments as creative research and teaching interventions and discuss the socio-cultural, pedagogic and political implications of our analysis for studies of participation in public settings, especially where stillness, silence and 'nothing' feature.